Performance Study of Installed an I-65o Type Cylinder at The Upstream of Returning Blade of Savonius Wind Turbine, Comparison With Conventional Savonius Wind Turbine - Gunawan Sakti; Triyogi Yuwono (IPTEK The Journal for Technology and Science, 2019)
Savonius wind turbine has many advantages over others in that its constructions are simpler and cheaper; it is independent of the wind direction and has a good starting torque at lower wind speeds. However, this type of wind turbine has the lowest performance compared to others types of wind turbine. That is why various studies have been done to improve the performance of the turbine Savonius. This paper is proposed in order to increasing the performance of Savonius wind turbine experimentally by installing an I-65o type bluff body at the upstream of returning blade of the turbine. The experiments are carried out for free stream velocity (U) of 7 m/s corresponds to Reynolds number of about 127.000 (based on the characteristic length of d = 2D-e and free stream velocity (U) from fan used. The center to center distance between the I-65o type cylinder and the returning blade turbine relative to turbine blade diameter S/D specified for 1.4. The diameter of I-65o type cylinder relative to turbine blade diameter is 0.5. The result of experimental show that in general compared to conventional Savonius wind turbines, the placement of I-65o type cylinder in front of the returning blade of the Savonius wind turbine is effective for improving turbine performance. The results of this experiment show that for Re = 127,000, the power coefficient of the turbine with the I-65o type cylinder is greater than when the turbine has no I-65o type cylinder or conventional Savonius wind turbine. Where in this condition, the maximum coefficient of power the Savonius turbine (CP) with I-65o type cylinder can actually increase to 25.66 % compared to the turbine without the I-65o type cylinder; this is obtained for Tip Speed Ratio of 0.76.